KEEFEKTIFAN BUKU ENSIKLOPEDIA FAMILI EUPHORBIACEAE UNTUK MELATIHKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA - Yunita, Lisa; Kaspul, Kaspul; Zaini, Muhammad (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2024)
One of the learning materials that is arranged alphabetically so that it is easy to use is an encyclopedia book. Encyclopedia development can train students' critical thinking skills in 21st century learning. This study aims to describe the practicality of the encyclopedia of the family euphorbiaceae. The research method used is Tessmer's formative evaluation design. The individual test subjects were 4 students who were taking the phanerogamae course and the small group test subjects were 4 students who were taking the phanerogamae course. Data were obtained from research instruments, practicality, content, and expectations. The results of the study show the practicality of category